1997
DOI: 10.1007/bf03339961
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of binge eating disorder in obese adults seeking weight loss treatment

Abstract: Binge eating has been identified as a common problem in samples of obese persons. Earlier studies found that approximately 30% of participants presenting for weight loss treatment could be diagnosed with Binge Eating Disorder (BED). This study investigated the prevalence of BED using the Questionnaire on Eating and Weight Patterns (QEWP) and the Interview for the Diagnosis of Eating Disorders (IDED) in a sample of 468 obese adults seeking weight loss treatment at two research facilities. The study found that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…Only one study was found that stratified the diabetes cohort (type 1 and 2 diabetic, male and female, ages 18–65 years) by weight status; 3% of under- and normal-weight women had a current eating disorder, whereas 7% of overweight and 10% of obese women had diagnosable eating disorders (27). These rates are similar to those for nondiabetic samples with similar BMI levels seeking weight loss (31). …”
Section: Prevalence Of Diagnosable Eating Disorders and Deb In Patiensupporting
confidence: 75%
See 2 more Smart Citations
“…Only one study was found that stratified the diabetes cohort (type 1 and 2 diabetic, male and female, ages 18–65 years) by weight status; 3% of under- and normal-weight women had a current eating disorder, whereas 7% of overweight and 10% of obese women had diagnosable eating disorders (27). These rates are similar to those for nondiabetic samples with similar BMI levels seeking weight loss (31). …”
Section: Prevalence Of Diagnosable Eating Disorders and Deb In Patiensupporting
confidence: 75%
“…Weight status is a strong predictor of eating disorders and DEB among overweight women attempting weight loss (31). Type 1 diabetic cohorts studied have been significantly heavier than comparison groups, with the average BMI above the normal range (1,19).…”
Section: Prevalence Of Diagnosable Eating Disorders and Deb In Patienmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, it is interesting to note that 3% of our student sample, and 12% of the EatRight weight-loss seeking sample obtained scores indicative of “severe binging”. These numbers approximate the estimated prevalence of BED in the general adult population (Hudson et al, 2007) and in weight-loss seeking populations (Dalle Grave, Calugi, Petroni, Di Domizio, & Marchesini, 2010; Hudson et al, 2007; Vamado et al, 1997). When we grouped participants into “none” and “moderate/severe” binge groups based on BES cut-offs for purely descriptive purposes, we found that scores on the PEMS motives were significantly higher in those classified as “moderate/severe” vs. “non-binge”.…”
Section: Discussionmentioning
confidence: 65%
“…Our study was based on a short self-report questionnaire that, although valid, included only three screening questions for BED. Thus, there is the possibility of having overestimated the prevalence of BED,44,45 and in future studies a structured clinical interview to assess BED may clarify this issue 46…”
Section: Discussionmentioning
confidence: 98%